2019
DOI: 10.2215/cjn.10640918
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Correction of Hypernatremia and Health Outcomes in Critically Ill Patients

Abstract: Background and objectivesHypernatremia is common in hospitalized, critically ill patients. Although there are no clear guidelines on sodium correction rate for hypernatremia, some studies suggest a reduction rate not to exceed 0.5 mmol/L per hour. However, the data supporting this recommendation and the optimal rate of hypernatremia correction in hospitalized adults are unclear.Design, setting, participants, & measurementsWe assessed the association of hypernatremia correction rates with neurologic outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 20 publications
2
54
0
8
Order By: Relevance
“…It is also possible that a fear of overly rapid correction of hypernatremia may explain why normal saline comprised 40% of the volume of fluids in patients with moderate hypernatremia in our study. The rate of correction is still debated but could have been quicker when there was an acute onset [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that a fear of overly rapid correction of hypernatremia may explain why normal saline comprised 40% of the volume of fluids in patients with moderate hypernatremia in our study. The rate of correction is still debated but could have been quicker when there was an acute onset [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the generally accepted treatment principle of hypernatremia may not be applicable to adults. In a recent study of more than 100 adult patients, although hypernatremia was corrected at a rate of 0.5 mEq/ L per hour or more (0.6-1.4 mEq/L per hour), no neurological complication such as seizure or brain edema occurred regardless of chronicity of the onset 13) . This study suggests that the reason why significant neurological complications do not occur even though hypernatremia is rapidly corrected in adult patients may be due to differences in brain capacity between adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Hypernatremia creates cellular dehydration and promotes peripheral insulin resistance, aggravating metabolic and immune disturbances, which might be the mechanism of development and exacerbation of infection [42,43]. Although the rate of hypernatremia relief still is controversial [44,45], it is suggested that patients can benefit from early identification and correction of post-operative hypernatremia as described in previous papers.…”
Section: Discussionmentioning
confidence: 99%